Onset Symptoms, Tobacco Smoking, and Progressive-Onset Phenotype Are Associated With a Delayed Onset of Multiple Sclerosis, and Marijuana Use With an Earlier Onset - Tao, Chunrong; Simpson, Steve; Taylor, Bruce V.; Blizzard, Leigh; Lucas, Robyn M.; Ponsonby, Anne-Louise; Broadley, Simon; , AusLong/Ausimmune Investigators Group; van der Mei, Ingrid; Lucas, Robyn M; Dear, Keith; Ponsonby, Anne-Louise; et al. (Frontiers in Neurology, 2018)
Background: Age at symptom onset (ASO) is a prognostic factor that could affect the accrual of disability in multiple sclerosis (MS) patients. Some factors are known to influence the risk of multiple sclerosis (MS), but their influence on the ASO is less well-investigated. Objective: Examine the associations between known or emerging MS risk factors and ASO. Methods: This was a multicentre study, incident cases (n=279) with first clinical diagnosis of demyelinating event aged 18–59 years recruited at four Australian centres (latitudes 27°S to 43°S), from 1 November 2003 to 31 December 2006. Environmental/behavioural variables and initial symptoms were recorded at baseline interview. Linear regression was used to assess the association between risk factors and ASO. Results: Five factors were significantly associated with ASO: a history of tobacco smoking was associated with 3.05-years later ASO (p=0.002); a history of marijuana use was associated with 6.03-years earlier ASO (p<0.001); progressive-onset cases had 5.61-years later ASO (p=0.001); an initial presentation of bowel & bladder and cerebral dysfunctional were associated with 3.39 (p=0.017) and 4.37-years (p=0.006) later ASO, respectively. Other factors, including sex, offspring number, latitude of study site, history of infectious mononucleosis, HLA-DR15 & HLA-A2 genotype, 25(OH)D levels, and ultraviolet radiation exposure were not associated with ASO. Including all five significant variables into one model explained 12% of the total variance in ASO. Conclusion: We found a novel association between a history of tobacco smoking and later onset, whereas marijuana use was associated with earlier onset. Behavioural factors seem important drivers of MS onset timing although much of the variance remains unexplained.